ArcGIS per l'ottimizzazione della rete vendita di ATAC - Ieradi, Michele; Molese, Guido; Perla, Annalisa; Leggeri, Flaminia; Raffaelli, Cristina; Matriciani, Daria (GEOmedia, 2009)
ATAC sales points network optimization through ArcGIS Atac SpA, the Mobility Agency of the City of Rome, by integrating its experience both in transport services and in the field of Geographic Information Systems, has made an effort to make information on the sales points network, for both PT and parking tickets, more effective and efficient. Through spatial analysis performed with specific GIS technology, Atac technicians highlighted some critical situations in the coverage of the network of sales. The analysis was performed by splitting the territory into homogeneous areas, then through the combination of all the spatial information available to Atac SpA it was possible to classify areas according to different parameters. All this helped to focus attention on areas where the sales network had lower efficiency and therefore through the application of GIS tools, the use of commercial databases and through site inspections on the territory it was possible to optimize the system.